2009
DOI: 10.22146/jp.12296
|View full text |Cite
|
Sign up to set email alerts
|

Kemiskinan Dan Usaha Mikro, Kecil, Dan Menengah

Abstract: This paper would like to see the role of UMKM (Usaha Mikro, Kecil, dan Menengah//W/cro, Small and Middle Scale Unit) in tackling poverty. The main superiority of UMKM in tackling poverty is in its ability to create working spaces. UMKM usually developed in the villages and created a new center of economical growth without eliminating the primary sector (agriculture). The developing of UMKM has been impeded since the government failed to understand the nature of UMKM itself. In framing the policies related to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…It means that if poverty increases, micro, and small businesses will also increase. These results are in line with Varma (1997); Walle (2000) in Retnandari (2009); ACS and Audretsch (1990) in Krisna (2016). Those studies revealed that micro and small business are considered capable of alleviating poverty by creating jobs because micro and small business is labor-intensive (Table 1).…”
Section: Figure 1 the Msmes Growth In Central Javasupporting
confidence: 84%
See 2 more Smart Citations
“…It means that if poverty increases, micro, and small businesses will also increase. These results are in line with Varma (1997); Walle (2000) in Retnandari (2009); ACS and Audretsch (1990) in Krisna (2016). Those studies revealed that micro and small business are considered capable of alleviating poverty by creating jobs because micro and small business is labor-intensive (Table 1).…”
Section: Figure 1 the Msmes Growth In Central Javasupporting
confidence: 84%
“…The previous studies above emphasize the importance of applying the new paradigm of SDGs to examine the relationship between poverty and small business. Studies by Varma (1997); Walle (2000) in Retnandari (2009); Ravallion (2016); Stewart (2019); ACS and Audretsch (1990) in Krisna (2016) emphasize the importance to note influence between poverty and small businesses. Meanwhile, Sjahrir (1983) Scoones (1998) with ownership of livelihood resources (education, health, electricity, etc.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation